FEEDING CHILDREN OF BREAST-FEEDING AGE - Umarkulov , Mukhtorali; Abdukahhorov , Muhammadqodir (Medical science of Uzbekistan, 2023)
This article discusses feeding infants and young children. The author describes three types of feeding children of breast-feeding age, namely, feeding with breast milk (natural way), mixed feeding with breast milk and complementary food, as well as artificial feeding informs about such methods.